Ecological characterization and conservation strategy of binjai (Mangifera caesia) in South Kalimantan, Indonesia - MUHAMMAD ADAM MALIK; AMIN SETYO LEKSONO; GUNAWAN GUNAWAN; SAIFUL ARIF ABDULLAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Malik MA, Leksono AS, Gunawan, Abdullah SA. 2025. Ecological characterization and conservation strategy of binjai (Mangifera caesia) in South Kalimantan, Indonesia. Biodiversitas 26: 3827-3842. Binjai (Mangifera caesia), a member of the Anacardiaceae family native to Southeast Asia, faces severe threats from timber extraction and habitat loss in South Kalimantan, Indonesia, while limited ecological data have hindered targeted conservation. This study assessed the distribution, ecological characteristics, and conservation strategies of binjai through field observations, purposive and snowball sampling, and ecological surveys in 21 plots (20×20 m each). Environmental factors measured included elevation, air temperature, humidity, light intensity, soil temperature, soil moisture, and soil pH, while vegetation data were collected using nested subplots across understory to tree levels and analyzed using Principal Component Analysis (PCA), vegetation analysis, and SWOT analysis. A total of 21 binjai trees were recorded in home yards, rice fields, and mixed gardens, with PCA revealing that air humidity (70.00-82.33%) and soil moisture (52.78-63.89%) were the most influential habitat factors. Vegetation surveys identified 74 associated species from 38 families, with dominant taxa including Cynodon dactylon and Oryza sativa in the understory, Caryota mitis and M. caesia at seedling level, Musa paradisiaca and Bambusa spinosa at sapling and pole levels, and Cocos nucifera and Durio zibethinus at the tree level. Diversity indices (H?=1.53-2.81) indicated moderate diversity across vegetation layers, reflecting ecological stability. The SWOT analysis highlighted weaknesses such as low community awareness and reliance on aged trees, as well as threats from land conversion and limited legal protection. Accordingly, recommended strategies include in situ protection through sustainable management and agroforestry integration, ex situ germplasm preservation in botanical gardens, environmental education to raise awareness, and cross-sector collaboration to enhance the conservation and economic value of binjai